Tannins and Anthocyanins: From Their Origin to Wine Analysis – A Review - Nel, A.P. (South African Journal of Enology and Viticulture, 2018)
Anthocyanins and tannins are very important chemical compounds in the grape berry and the corresponding wine, as they greatly influence the colour, taste and maturation potential of the wine, as well as offer numerous health benefits. This review tries to establish the origin of anthocyanins and tannins by looking at metabolic pathways and attempting to establish a link between photosynthesis and the flavonoid biosynthetic pathway, the translocation thereof from leaves to berries, different methods to extract anthocyanins and tannins from wine and, in the end, the different analytical methods that can be used to analyse for anthocyanins and tannins.